Stuxnet balances mitochondria homeostasis by regulating uhg5 and parkin. - Zhao, X.; Yang, X.; Huang, Y.; Zhang, Y.; Cui, X.; Zhang, J.; Du, J. (Cell reports, 2026)
Emerging evidence implicates the Stuxnet (Stx) protein in human disease, extending beyond its known role in proteasome-independent degradation. Exploring this further, our investigation into stx downstream targets in Drosophila reveals that loss of the U snoRNA host gene 5 (Uhg5) gene disrupts sleep. This sleep phenotype is linked to inefficient translation of mitochondrial genes, as Uhg5 produces small nucleolar RNAs (snoRNAs) that directly regulate mitochondrial transcripts. Using GoldCLIP technology, we discover that Stx interacts with both Uhg5 and parkin mRNAs. parkin is a key regulator of mitochondrial quality control. Genetic tests confirm functional relationships between stx, Uhg5, and parkin. This study establishes that Uhg5-derived snoRNAs regulate sleep by controlling mitochondrial gene translation. Crucially, our findings propose a model in which Stx coordinates mitochondrial biogenesis (via Uhg5) with mitophagy (via parkin). This provides a molecular link for Stx's potential role in Parkinson's disease pathogenesis.